A splice-site variant in FLVCR1 produces retinitis pigmentosa without posterior column ataxia - Yusuf, Imran H. (Ophthalmic Genet, 2017)
FLVCR1 (feline leukaemia virus subgroup c receptor 1) is a transmembrane protein involved in the trafficking of intracellular heme. Homozygous variants in FLVCR1 have been described in association with a clinical syndrome of posterior column ataxia with retinitis pigmentosa (PCARP). Here we describe a patient with non-syndromic retinitis pigmentosa homozygous for a splice-site variant in FLVCR1 (c.1092+5G>A) without evidence of posterior column ataxia or cerebellar degeneration. We suggest an association between intronic splice-site variants in FLVCR1 and the absence of posterior column degeneration and suggest an hypothesis to explain this observation. Should this association be proven, it would provide valuable prognostic information for patients. Retinal degeneration appears to be the sole clinical manifestation of this FLVCR1 variant; gene therapy approaches using an adeno-associated viral vector with sub-retinal delivery may therefore represent a therapeutic approach to halting retinal degeneration in this patient group.